Ecology and diversity of macrobenthic communities in Pozhikkara estuary - Parvathy, S. (KUFOS, 2019)
Abstract- Benthic organisms form one of the important ecological components in the estuarine ecosystem. Their abundance, distribution and diversity varies on spatial and temporal scales. In the present study, seasonal variations in distribution and diversity of macro-benthic organisms were studied in Pozhikara Estuary, southwest coast of India (Lat. . ). This is a blind estuary; having an average depth of 2.23±0.31m nai ardae tdw w s ion dna snnildaae ro saw re tsos braiebwsi esneranllo nw reo ewnwdrae srwsaidaa orn eiewosnn osadra wr nonrew from April 2018 wrNovember 2018. Environmental parameters were also recorded. Major groups of benthic organisms observed were polychaetes, crustaceans, bivalves and gastropods. Among these crustaceans were the most abundant group followed by polychaetes. This is an attempt to correlate the environmental parameters with benthic organism. Salinity shows a negative correlation with total organism. Among the different polychaete family observed Nereidae, Eunicidae shows a positive correlation with percentage silt (p<0.01). With organic matter Eunicidae shows a positive correlation while Pisionidae shows a negative correlation (p<0.01). This is a sand dominant estuary with relatively less amount of organic matter, so can be stated as a relatively undisturbed area.